CLINICO-ECONOMICAL ANALYSIS OF THE TREATMENT EFFICACY IN PATIENTS WITH ARTERIAL HYPERTENSION OF 1-2 DEGREES - L. A. Haisheva; S. V. Shlyk; T. Y. Bykovskaya (Рациональная фармакотерапия в кардиологии, 2016)
Aim. Clinico-economical analysis of arterial hypertension (HT) treatmentMaterial and methods. 78 patients with HT were involved into the study. Patients were spitted into two groups depending on HT degree. The first group – 38 patients with HT 1 degree. The second one – 40 patients with HT 2 degree. Patients of group 1 had initial antihypertensive therapy with angiotensinconverting enzyme inhibitors. If target level of blood pressure (BP) had not been reached, therapy was changed on fixed combination of lisinopril and hydrochlorothiazide. Patients of group 2 had initial combined antihypertensive therapy with lisinopril and hydrochlorothiazide. If it was needed amlodipine maleat was added. Clinico-economical analysis was performed according to “cost-efficacy” approach at the end of 3 month therapy.Results. About 50% of hypertensive patients do not follow physician recommendations in out-patient practice. They decrease a dose of medicine or stop therapy themselves. More than 6% of them perform self-treatment.Conclusion. Analysis showed that therapy of patients with HT of 1 degree is economically more profitable regarding target BP achievement. It is more reasonable to start antihypertensive therapy with fixed low dose combination and add calcium antagonists if it is needed in patients with HT of 2 degree.